In-depth exploration of the radiation exposure to staff performing endoscopic retrograde cholangiopancreatography procedures (ERCP) through RANDO phantom and TLDs - Kesmezacar, Fahrettin Fatih; Tuncman, Duygu; Nayci, Ali Emre; Gunay, Osman; Yeyin, Nami; Uzum, Gungor; Demir, Mustafa; Akkus, Baki; Elshami, Wiam; Almisned, Ghada; Tekin, H. O. (SPRINGER, 2024)
This study provides a comprehensive evaluation of the occupational radiation exposure faced by healthcare professionals during Endoscopic Retrograde Cholangiopancreatography (ERCP) procedures. Utilizing an anthropomorphic RANDO phantom equipped with Thermoluminescent Dosimeters (TLDs), we replicated ERCP scenarios to measure radiation doses received by medical staff. The study meticulously assessed radiation exposure in various corresponding body regions typically occupied by medical staff during ERCP, with a focus on eyes, thyroid, hands, and reproductive corresponding organ regions. The findings revealed significant variations in radiation doses across different body parts, highlighting areas of higher exposure and underscoring the need for improved protective measures and procedural adjustments. The effective radiation doses were calculated using standard protocols, considering the varying levels of protection offered by lead aprons and thyroid shields. The results demonstrate the substantial radiation exposure experienced by healthcare staff, particularly in regions not adequately shielded. This study emphasizes the necessity for enhanced radiation safety protocols in clinical settings, advocating for advanced protective equipment, training in radiation safety, and the exploration of alternative imaging modalities. The findings have crucial implications for both patient and staff safety, ensuring the continued efficacy and safety of ERCP and similar interventional procedures. This research contributes significantly to the field of occupational health and safety in interventional radiology, providing vital data for the development of safer medical practices.
Keywords: Radiation protection; ALARA; RANDO; ERCP; Occupational dose; PATIENT; TRENDS; Radiology, Nuclear Medicine & Medical Imaging